Remote sensing and its applications - Narayan, L. R. A.; International Council of Scientific Unions. Committee on Science and Technology in Developing Countries (New Delhi : Universities Press (India) : Distributed by Orient Longman, 1999)
With reference to India.
"COSTED."
Keywords: Remote sensing -- India; Artificial satellites in remote sensing